Examining financial management in Thai public schools: sources of funding, allocation practices, and strategies for improvement - Jakkrit Marnnoi; Tanate Panrat; Hambalee Jehma (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study was conducted to address the critical gaps in financial management practices within Thai public schools, where inefficiencies and mismanagement persist despite available guidelines and funding. The relevance of this research lies in its potential to enhance financial governance, ensuring optimal resource allocation and accountability, which are vital for improving educational outcomes. Employing a mixed-methods approach, the study combined descriptive questionnaires administered to 396 school administrators with structured interviews involving 36 participants to evaluate funding sources, allocation processes, and adherence to financial guidelines. The findings revealed that while schools received funding from diverse sources, namely government, parents, and donors, 85% of administrators reported insufficient budgets. Notably, 82% acknowledged non-compliance with financial guidelines despite submitting utilization reports, highlighting systemic inefficiencies. The study concluded that inadequate financial management skills and inconsistent policy implementation hinder effective resource use. To address these challenges, the study proposes targeted interventions, including specialized training programs, the establishment of dedicated financial departments, and updated management guidelines. These measures aim to strengthen financial accountability and operational efficiency in public schools, offering actionable insights for policymakers and administrators. Future research should compare public and private sector practices to refine standardized financial management frameworks.